2017
DOI: 10.1016/j.ijfoodmicro.2017.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Variations in biofilm formation, desiccation resistance and Benzalkonium chloride susceptibility among Listeria monocytogenes strains isolated in Canada

Abstract: Listeria monocytogenes is a pathogenic foodborne microorganism noted for its ability to survive in the environment and food processing facilities. Survival may be related to the phenotype of individual strains including the ability to form biofilms and resist desiccation and/or sanitizer exposure. The objectives of this research were to compare 14 L. monocytogenes strains isolated from blood (3), food (6) and water (5) with respect to their benzalkonium chloride (BAC) sensitivity, desiccation resistance, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…However, controversial results for the effects of cell surface hydrophobicity on biofilm formation on cell contact surfaces have been reported because biofilm formation depends on several factors [49], such as temperature. To this effect, it has been observed that biofilm formation is greater at temperatures above 20 • C than at refrigeration temperatures, for example 12 • C, the temperature used in this study [15,44,50,51].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, controversial results for the effects of cell surface hydrophobicity on biofilm formation on cell contact surfaces have been reported because biofilm formation depends on several factors [49], such as temperature. To this effect, it has been observed that biofilm formation is greater at temperatures above 20 • C than at refrigeration temperatures, for example 12 • C, the temperature used in this study [15,44,50,51].…”
Section: Discussionmentioning
confidence: 81%
“…Cells in biofilms become more resistant than planktonic cells to different environmental stress factors such as sanitizing agents, facilitating bacterial survival. Furthermore, biofilms can be a continuous source of contamination when in contact with foodstuffs, which can trigger human disease [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Also, there were no significant (p > 0.05) differences between the model parameters when the survival kinetics of the two strains were compared using the Weilbull model (Mafart et al, 2001) (data not shown). Lm 08-5578 has previously been shown to display increased desiccation tolerance compared to Lm 568 in desiccation trials at 23% RH and 15 • C (Piercey et al, 2017), indicating that Lm 08-5578 may have an advantage at a lower RH.…”
Section: Survival Of L Monocytogenes During Desiccation On Stainlessmentioning
confidence: 98%
“…Listeria monocytogenes is capable of surviving in various adverse environments, such as low temperature, high salinity, and a wide range of pH values ( Gandhi and Chikindas, 2007 ). In addition, L. monocytogenes biofilm exhibits a strong ability to resist disinfectants, resulting in persistent contamination of food plants ( nakamura et al, 2013 ; Piercey et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%